Plan de negocio joyería Gracia (2020)
This project is an attempt to formalize Gracia's jewelry, which has been working with informality, and yet has achieve great results. The above mentioned is based on the idea that Colombian jewelry industry is very promising but for the lack of interest and investment has not been exploited to its full potential. Through an investigation and marketing studies, the economic and financial feasibility is evident in Colombia. We want to show that is possible to be pioneers with success on personalized jewelry, both in design and customer service. Taking advantage of this market through the mass sales and offering added value such as promoting employment and training the employees on jewel knowledge in the company.